Use of chromogenic Agar in detection of urinary tract pathogens and antimicrobial Susceptibility - Abdullah, Arwa M.; Abdullah, Rana M.; Salman, Shaymaa L. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: HROM agar Orientation is a chromogenic medium used for the detection and differentiation of Gram’s negative and Gram’s positive pathogenic microorganisms in urine samples. Evaluation of CHROM agar Orientation for identification of urinary pathogens and susceptibility determinations in comparison to the ordinary media used. Patients and Methods: A total of 375 midstream urine sample collected from patients with urinary tract infection (UTIs). CHROM agar Orientation, blood agar and macConkey agar media were used for direct inoculation. Results: CHROM agar Orientation succeeded in detecting all the urine pathogens that were detected by the reference media, and antimicrobial Susceptibility tests were performed directly from primary isolates in all cases without the need for subcultures. Conclusion: HROM agar Orientation medium excellent detection of urinary pathogens and antimicrobial Susceptibility tests without the need for subcultures. Therefore, can replace the standard primary plating media used in routine diagnosis of urinary tract infection.